Formação de aplicadores e interlocutores na utilização do PECS-Adaptado para crianças/adolescentes com autismo - Evaristo, Fabiana Lacerda (Universidade Federal de São Carlos, 2016)
Communication is one of the most important factors related to the quality of life of people with the diagnosis of autism, which can be absent or dysfunctional, with or without speech. Due to the importance of communication for humans to establish social exchanges, this study aims to evaluate the efficacy of an applicants and interlocutors training program for use of PECS-Adaptado in children /adolescents with autism spectrum disorder. The participants were three students not oralized and/or no functional speech. The criterion for the selection of participants in this study was based on the searching for students not oralized and/or no functional speech who presented diagnosis of autism spectrum disorder and does not presented visual and/or hearing impairment, in a midsize city located within the state of São Paulo. The classroom was attended by the teacher (PP1) of the participating students (PA1 and PA2) and the mother (PM3) of one of the participating students, who were qualified as interlocutors through teaching procedures of PECS-Adaptado program. It was used intermittently design of multiple baseline between participants, in which the subject acts as his own control. Family members of participants provide data for research according to the semi-structured initial interview guide and the list of participant’s interests. At the end of the sessions with the phase 3, the PA1 and PA2’s relatives were invited to follow the activities with their children at school, in order to also becoming immediate interlocutors. PM3 attended all sessions and another relative (father PA3) monitored the activities from stage 3. The interventions were conducted in a classroom of a special education school with the PA1 and PA2 by interlocutor PP1, and the house of PA3 by interlocutor PM3. The records protocols with PECS-Adaptado’s phases were used to record the performance of the participants. It was also used a record protocol for the interlocutors in order to recognize their performance through the opportunities offered to the participants. The results indicate that, after the application of interlocutors training program with the teacher and with the mother, the participating students presented satisfactory development of communication by exchange of figures. During the survey, participating students increased their communication skills, according to their needs and their desires through the interference of the interlocutors, who had an important role in the achievement of the program's effectiveness. The applicants and interlocutors, in addition of being capacitated, also understood the importance of using the alternative communication program for teaching and learning.
Keywords: Educação especial; Transtorno do espectro do autismo; Comunicação alternativa; Formação de interlocutores; Special education; Autism spectrum disorder; Alternative communication; Training interlocutors; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM